2021
DOI: 10.1021/acs.inorgchem.0c03804
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Different Roles of Rare Earth Ions in the Crystallization of Upconversion Oxyfluoride Glass Ceramics by Solid-State Nuclear Magnetic Resonance Spectroscopy

Abstract: Rare earth ion-doped oxyfluoride glasses in the system 50SiO 2 −(50 − x)PbO−xPbF 2 −mLa 2 O 3 −nEr 2 O 3 were prepared by the melt-quenching method. PbF 2 and LaF 3 were selectively crystallized by subsequent heat treatment in these glasses. The promotion and suppression effects of La 3+ ions on the crystallization of PbF 2 were observed in this selective crystallization. We used advanced solid-state nuclear magnetic resonance (NMR) and X-ray diffraction techniques to probe the structural evolution in the atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is generally accepted that the composition of the crystallite nuclei is purely governed by the distribution of glass-former and modifying additives inside the glass network. Yu et al 54 has reported that distribution of RE 3+ ions in the glass matrix plays a crucial role during the ceramization of glass. In LGTT glass, it is assumed that La, Gd and doped trivalent RE ions are distributed homogeneously.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the composition of the crystallite nuclei is purely governed by the distribution of glass-former and modifying additives inside the glass network. Yu et al 54 has reported that distribution of RE 3+ ions in the glass matrix plays a crucial role during the ceramization of glass. In LGTT glass, it is assumed that La, Gd and doped trivalent RE ions are distributed homogeneously.…”
Section: Discussionmentioning
confidence: 99%
“…F1 signal can be assigned to the F in the La–F‐Ba linkage. [ 33 ] Both F2 and F3 signals are related to F species involved in the F‐Al linkages of Al‐F‐Al and Na‐F‐Al, respectively. [ 34,35 ] Upon HT, the F1 resonance shifts from −12 to –18 ppm, indicating that some of the F ions participate in the formation of the Ba 2 LaF 7 crystals, rather than stay in the glass matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, we only observed the competition between the cations to attract F − . In the glass with the composition 50SiO 2 −40PbO−10PbF 2 −1La 2 O 3 , 35 La 3+ demonstrated stronger ability than Pb 2+ to attract F − . Thus, the LaF 3 crystals were preferentially precipitated, while the precipitation of PbF 2 was suppressed by La 3+ .…”
Section: Na Tq Mas Nmrmentioning
confidence: 99%
“…Recently, we studied Er 3+ -doped 50SiO 2 –40PbO–10PbF 2 –1La 2 O 3 and 55SiO 2 –10Al 2 O 3 –10CaO–20CaF 2 –5La 2 O 3 glasses. We attempted to precipitate PbF 2 and CaF 2 crystals from these two glasses, respectively, after which rare-earth (Re) ions could be homogeneously incorporated into the crystals.…”
Section: Introductionmentioning
confidence: 99%